NFκB1 inhibits memory formation and supports effector function of ILC2s in memory-driven asthma - Verma, Mukesh; Verma, Divya; Sripada, Anand Santosh; Sirohi, Kapil; Varma, Rangati; Sahu, Anita; Alam, Rafeul (Frontiers in Immunology, 2023)
Background: ILC2s are capable of generating memory. The mechanism of memory induction and memory-driven effector function (trained immunity) in ILC2s is unknown. Objective: NFκB1 is preferentially expressed at a high level in ILC2s. We examined the role of NFkB1 in memory induction and memory-driven effector function in a mouse model of asthma. Methods: Intranasal administration of Alternaria, flexivent, ELISA, histology, real-time PCR, western blot, flow cytometry and immunofluorescence staining. Results: NFκB1 was essential for the effector phase of memory-driven asthma. NFκB1 was critical for IL33 production, ILC2 generation, and production of type-2 cytokines, which resulted in eosinophilic inflammation and other features of asthma. NFκB1 induction of type-2 cytokines in ILC2s was independent of GATA3. NFκB1 was important for allergen induction of ILC3s and FoxP3+ Tregs. NFκB1 did not affect Th2 cells or their cytokine production. In contrast to its protagonistic role in the effector phase, NFκB1 had an antagonistic role in the memory phase. NFκB1 inhibited allergen-induced upregulation of memory-associated repressor and preparedness genes in ILC2s. NFκB1 upregulated RUNX1. NFκB1 formed a heterodimer with RUNX1 in ILC2s. Conclusions: NFκB1 positively regulated the effector phase but inhibited the induction phase of memory. The foregoing pointed to an interdependent antagonism between the memory induction and the memory effector processes. The NFκB1-RUNX1 heterodimer represented a non-canonical transcriptional activator of type-2 cytokines in ILC2s. Key words: Asthma, IL2s, memory, IL33, NFκB1, and RUNX1